Endoscopic Resection of Vestibular Schwannomas - Setty, Pradeep; D'Andrea, Kenneth P.; Stucken, Emily Z.; Babu, Seilesh; LaRouere, Michael J.; Pieper, Daniel R. (Journal of Neurological Surgery Part B: Skull Base, 2015)
Objective To report our results and the technical details of fully endoscopic resection of vestibular schwannomas.Design Prospective observational study.Setting A single academic institution involving neurosurgery and neurotology.Participants Twelve consecutive patients who underwent fully endoscopic resection of a vestibular schwannoma.Main Outcome Measures Hearing preservation, based on the American Association of Otolaryngology-Head and Neck Surgeons (AAO-HNS) score as well as the Gardener and Robertson Modified Hearing Classification (GR). Facial nerve preservation based on the House-Brackmann (HB) score.Results All patients successfully underwent gross total resection. Facial nerve preservation rate was 92% with 11 of 12 patients retaining an HB score of 1/6 postoperatively. Hearing preservation rate was 67% with 8 of 12 patients maintaining a stable AAO-HNS grade and GR score at follow-up. Mean tumor size was 1.5 cm (range: 1–2 cm). No patients experienced postoperative cerebrospinal fluid leak, infection, or cranial nerve palsy for a complication rate of 0%. Mean operative time was 261.6 minutes with an estimated blood loss of 56.3 mL and average length of hospital stay of 3.6 days.Conclusion A purely endoscopic approach is a safe and effective option for hearing preservation surgery for vestibular schwannomas in appropriately selected patients.
Keywords: acoustic neuroma; cerebellopontine angle; endoscopy; skull base; vestibular schwannoma